EMPOWERMENT OF PRODUCT PROCESSING, LICENSING, AND MARKETING ON MICRO-ENTERPRISE OF IBU NYAI’S PISANG SALE - Wisnu Pamungkas; Ilham Muharexza; Fadly Syafarulloh; Fenia Apriliani Putri; Monica Setia Almira; Velita Velita; Aminullah Aminullah (LP2M Universitas Ibrahimy, 2024)
This service activity aimed to provide essential knowledge and information related to sanitation and marketing included licensing, which must be applied to micro-enterprises to be able to produce food products properly and safely. The Participatory Action Research approach was used in service activities focusing on empowering micro-enterprises. The service activities were coordinating with village officials, determining the site, observing the problems, and conducting the program activity. There were two programs namely the main program was socialization regarding sanitation and hygiene and its application in the production of pisang sale; and the supporting program was making a Business Certificate from the village, a Business Permit Number, flowcharts of the production process, product logos, and helping promote these products. The results included micro-enterprise owners who understand the importance of sanitation in the production process, such as washing hands before production, using head coverings, masks, gloves, aprons, special clothes for production, and wearing boots. In addition, business actors already have business legalities, such as Business Permit Number and Business Certificate, and have a better logo on their product. Marketing has been more developed by utilizing social media, namely WhatsApp, so product sales have become more expensive.